Substance use, fear of future HIV infection and quality of life of household heads in rural and semi Urban communities of Ibadan, (2015)
Quality of life (QOL) among household heads is important because it may serve as a mirror to underlying family psychopathology and well-being. This study examined pattern of quality of life of household heads and the role of substance use (tobacco and alcohol) in the impact of fear of HIV infection on quality of life among household heads in Nigeria. Five hundred and seventy nine (male: 77%; female 24%) household heads with mean age 43.9± 12.23 participated in the study. Mean quality of life were (24.64, SD = ±4.80) for physical (10.73, SD = ±2.11) for social, (24.57, SD =±4.56); for environmental, and (21.44, SD = ±4.11) for psychological). Multivariate analysis showed a significant effect of fear of future HIV infection on physical [F (3,564) = 13.367, p < .05}, and social [F (3,564) = 3.12, p < .05} qualities of life of household head respectively. A significantly effect of tobacco use was also observed on environmental quality of life [F (1, 564) = 85.313, p < .05}. A significant interaction effect of fear of future HIV infection and either alcohol or tobacco use on physical quality of life [F (2, 564) = 16.921 P < .05} was observed. Also shown was a significant interaction effect of alcohol and tobacco usage on the physical [F (1, 564) = 14.986, P < .05} as well as social [F (1,564) = 5.992, p < .05} qualities of life of the household heads. It was concluded that substance use (tobacco and alcohol use) may attenuate the impact of fear of future HIV/AIDS infection on quality of life of household heads in Ibadan, Nigeria.